Mō̜radok phūmpanyā thāng watthanatham khō̜ng chāt : phithī prakāt khưn thabīan mō̜radok phūmpanyā thāng watthanatham khō̜ng chāt pračham pī Phutthasakkarāt 2555, Wansuk thī 14 Thanwākhom Phutthasakkarāt 2555 na hō̜ prachum lek, Sūn Watthanatham hǣng Prathēt Thai, Krom Songsœ̄m Watthanatham, Krasūang Watthanatham (Krom Songsœ̄m Watthanatham, Krasūang Watthanatham, 2012)
On civilization, manners and customs of Thailand.